A Comparative Study of Activity-Based Costing vs. Current Pricing System for Pathology Examinations at Okmeydani Training and Research Hospital, Turkey - Enver YARIKKAYA; Selver ÖZEKİNCİ; Aytül SARGAN; Şenay ERDOĞAN DURMUŞ; Fetin Rüştü YILDIZ (Federation of Turkish Pathology Societies, 2017)
Objective: To provide real cost data for pathology examinations by using activity-based costing method, in order to provide means to departments, health administrators and the social security institution to achieve improvements in financial planning, quality and cost control. Material and Method: The cost of the histopathological examinations, which were accepted by the Department of Pathology at Okmeydanı Training and Research Hospital during August 2014, was calculated using the activity-based costing method. The costs were compared with the amounts specified in the Healthcare Implementation Notification Tariff and the conventional volume-based costing. Results: Most pathology examinations listed within a given band in the Healthcare Implementation Notification Tariff show variations in unit costs. The study found that the costs of 77.4% of the examinations were higher than the prices listed in the Healthcare Implementation Notification Tariff. Conclusion: The pathology examination tariffs specified in the Healthcare Implementation Notification do not reflect the real costs of the examinations. The costs that are calculated using the activity-based costing system may vary according to the service types and levels of health care institutions. However, the main parameters of the method used in the study reflect the necessity of a more accurate banding of pathology examinations. The banding specified by the Healthcare Implementation Notification Tariff needs to be revised to reflect the real costs in Turkey.